Политичката идеологија на македонската емиграција во Санкт Петербург 1913 во контекст на современата епистема - Banovikj-Markovska, Angelina (МАКЕДОНСКА АКАДЕМИЈА НА НАУКИТЕ И УМЕТНОСТИТЕ, 2023)
The topic of the essay is the testimonial discourse of the two Memoranda for the independence of Macedonia, published by the members of the Macedonian Scientific and Literary Society in St. Petersburg, 1913. Interpreted from the perspective of the contemporary episteme, these strategic documents sublimate the Macedonian scientific, cultural and national thought. They represent, on the one hand, a legitimate legal act with which a group of intellectuals promotes their ideology (a legal-political doctrine with a dominant ethno-cultural matrix and a system of values that reflects the developments in the years before and after the First Balkan War), and, on the other, they represent a diplomatic testimony of the efforts of the Macedonian emigration in Russia to lay the foundations of an unofficial foreign policy. Their interpretation also aims to show that, apart from the sound of the anamnesis, one should also listen to the muffled echo of its silence which, defying historical amnesia, constantly refreshes the nation's cultural memory. Therefore, even though they were written eleven decades ago, the memoranda texts for the independence of Macedonia from 1913 are at the same time meta-testimonies for the moral dilemmas faced by Macedonian historical science today, when interpreting the historical narratives that build the anamnestic infrastructure of the national memory.
Keywords: memorandum; independence; Macedonia; political ideology; nationalism; epistemology; national memory